Global burden of cancer in women, 1990–2021: a systematic analysis from the GBD 2021 study - Mao, Yun; Gao, Yebo; He, Yongjie; Wan, Zuihui; Li, Shuyu; Ding, Zhixun; Hu, Beier; Fu, Ling; Luo, Chao; Zhu, Shijie; Cao, Wen (Frontiers in Oncology, 2025)
ObjectiveThis study evaluates global burden, disparities, and trends of female cancers (breast, cervical, uterine, ovarian) from 1990 to 2021, and identifies key contributing factors and intervention strategies.MethodsData from the Global Burden of Disease (GBD,1990–2021) Study and recent reports were analyzed to assess incidence, mortality, and disability-adjusted life years (DALYs) across 204 countries stratified by Socio-demographic Index (SDI). Regression and spatiotemporal analyses explored links with risk factors (e.g., obesity, HPV) and healthcare access.ResultsBreast cancer dominated the burden, with age-standardized incidence rates (ASIR) rising by 28% (2.08 million new cases in 2021), driven by lifestyle factors (high BMI, alcohol use) and showing a strong connection with higher SDI (r=0.82). Cervical cancer remained a critical challenge in low- and middle-income regions, showing a strong negative correlation with SDI(r = -0.75), though Age-Standardized Mortality Rate (ASMR) declined globally (-1.4% annual change). Uterine cancer incidence rose steadily (0.7% annual increase; 473,614 cases in 2021), primarily attributable to obesity, while ovarian cancer mortality remained high (207,000 deaths) due to late diagnosis. Key modifiable risks included HPV infection (85% of cervical cancers), tobacco use, and reproductive behaviors.ConclusionThe global burden of female cancers presents a significant public health challenge. Disparities in female cancer burden reflect inequities in healthcare access and rising metabolic risks. Priority actions include HPV vaccination, low-cost screening, and obesity control. Equity-focused, data-informed policies are crucial to reduce global disparities.